Uncertainty and LR: to integrate or not to integrate, that's the question. (11th September 2015) - Sjerps, M. J.; Alberink, I.; Bolck, A.; Stoel, R. D.; Vergeer, P.; van Zanten, J. H.
Abstract : Taroni et al. (2016) discuss the controversial issue of parameter uncertainty in the context of forensic evidence evaluation. Although we share with the authors the main idea that the likelihood ratio (LR) framework is the best method for evaluating forensic evidence, we have a different view on this issue. The core question is: does it make sense to consider the uncertainty attached to a calculated value of the LR, and consequently, should we report a single value for the LR or in addition address its uncertainty? Taroni et al. (2016) argue for reporting a single value based on a 'full-Bayesian' approach, and accuse anyone who considers the uncertainty of an LR of 'misconception of basic principles' and 'abuse of language'. However, their arguments presented as facts or logic are in fact choices or opinions. Furthermore, reporting a single number for the LR deprives the legal justice system of essential information needed to assess the reliability of the evidence. Therefore, we argue that forensic scientists should not only report an LR value, but also address its uncertainty and we explain why this is not a misconception or abuse of language.